Use of Anionic Surfactant-Modified Activated Carbon for Efficient Adsorptive Removal of Crystal Violet Dye - Rumi Goswami; Amit Kumar Dey (Adsorption Science & Technology)
Studies have been carried out to investigate the removal of crystal violet (CV) cationic dye by using rice husk which was used as a raw material to prepare activated carbon (AC) and it was treated with anionic surfactant. In this process, AC was treated with three different anionic surfactants, namely, lauryl sulfate ACMAS, ACSDS, and ACHTAB. Characterization and analysis of optimum ACMAS were done using different techniques which were used which proves the adsorption of the dye by ACMAS. Effects of various physical parameters like time of contact, additive salts, initial dye concentration, effect of pH, and effect of adsorbent dose were studied. Minute changes in the dye removal capacity were observed due to the presence of various cations. Cations like NO2- caused an increase in the capacity of adsorption but cations like Fe2+decreased the capacity of adsorption in the sample solution. The effectiveness of film diffusion and intraparticle has been shown by mass transfer parameters. The various kinetic studies have shown that pseudo second-order kinetic study best suited with the experimental data. Error analysis and studies of isotherms have shown that the adsorption equilibrium was controlled by Langmuir isotherm study with maximum CV dye adsorption capacity of 235.7 mg/g. Thermodynamics studies revealed endothermicity of the process with negative ΔG values and positive ΔS and ΔH values. Activation energy of 48.31 kJ/mol suggested chemisorption process of the system. Column studies were carried out by using different models to study the variation of bed depth, dye concentration, flow rate, etc. Regeneration experiments have given the ability of the adsorbent to be reused. In this present study, it has been noticed that the use of anionic surfactant-treated activated carbon significantly improved the adsorption of dye and this is a process of adsorption in which not much attention has been given for research till date.